Sehat Bersama Masyarakat Sejahtera: Pemeriksaan Dan Penyuluhan Kesehatan Upaya Mendukung Kesejahteraan Lansia - Zuriati, Zuriati; Imelda Avia; Rina Librianty; Rias Wildan (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2025)
The increasing number of elderly people in Indonesia brings major challenges in the field of public health, especially related to the prevalence of degenerative diseases such as hypertension, diabetes mellitus, high cholesterol, and gout. The elderly group is often unaware of the importance of early detection and prevention of these diseases. The purpose of this activity is to increase awareness, knowledge, and concern for the health of their elderly, as well as a form of active role of universities in community service. This activity was carried out using the counseling and health examination method involving lecturers and students from STIKes Bhakti Husada Cikarang. The examination included blood pressure, random blood sugar levels, cholesterol, and uric acid, as well as education about healthy lifestyles provided in the form of presentations and leaflets. This activity was carried out on February 25, 2025. The results of the activity showed an increase in participants' understanding of degenerative diseases and their preventive measures, as indicated by an increase in pre-test and post-test scores by 35%, and an increase in the participation of the elderly in routine health checks by 45%. Health cadres were also formed to assist in the implementation of sustainable activities at the RT/RW level. Suggestions given included the importance of implementing regular counseling, increasing cross-sector cooperation such as health centers and RT/RW, and strengthening cadres as the spearhead of public health promotion. Similar activities are highly recommended to include them in order to realize a healthy, independent, and prosperous elderly society.